(untitled) (Al-Academy, 2021)
The current research is summarized by studying and understanding the imagination and what resulted from it in postmodern arts, specifically Pop Art. The research was focused spatially (America) between the year 1950-1975 AD and it defined the research problem by asking about what factors and variables that established the social imagination in culture Al-Gharbia, which in turn crystallized the Western cultural product to appear in its form, which is historically called "pop art". Two studies were adopted in the second chapter. The first one was the cultural structure of the social imagination. The second topic was concerned with the stylistic diversity of pop art, and the third chapter included research and accreditation procedures. There are two models for determining the research sample, and the research has produced results in the fourth semester, the most important of which are:• The artworks of pop art depended on the culture of society, the environment, consumer materials, advertisements, existential concepts and artistic methods represented by Dada, which represented the gathering of the different in which the artist relied on the imagination to achieve a thrill that achieves astonishment for the recipient.• Imagination as a system of thought depends on form and reality on references whose origin is from finished goods, materials, and furniture, which is one of the most important characteristics of Pop Art.And lastly were the conclusions and the list of sources